2016
DOI: 10.1177/1477153515581412
|View full text |Cite
|
Sign up to set email alerts
|

Scene brightness of illuminated interiors

Abstract: It is important to be able to engineer the brightness of interior spaces. In addition to the amount of light delivered to and reflected from surfaces in the space, light spectrum influences apparent scene brightness. Specifically, spaces illuminated by ‘cool white’ sources will look brighter than those illuminated by ‘warm white’ sources for the same photopic light levels. A scale model residential space was used to obtain judgements of scene brightness where light levels, surface reflectances and light source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 22 publications
4
46
0
Order By: Relevance
“…5,7-12 A provisional model of apparent scene brightness has been recently published so that for any SID (both spectrum and amount), the apparent brightness of a scene can be predicted. [9][10][11][12]18 Moreover, a direct link has been shown between apparent brightness and perceived sense of safety and security, 16 and the present results confirm this link. In principle then, the body of research makes it possible to optimise the benefits and costs of outdoor lighting by taking into account the SID of illumination.…”
Section: Discussionsupporting
confidence: 92%
“…5,7-12 A provisional model of apparent scene brightness has been recently published so that for any SID (both spectrum and amount), the apparent brightness of a scene can be predicted. [9][10][11][12]18 Moreover, a direct link has been shown between apparent brightness and perceived sense of safety and security, 16 and the present results confirm this link. In principle then, the body of research makes it possible to optimise the benefits and costs of outdoor lighting by taking into account the SID of illumination.…”
Section: Discussionsupporting
confidence: 92%
“…28, 29 Rea et al found illuminance on a vertical plane to correlate better with assessments of brightness than that of light on a horizontal plane. 27 In two separate studies, Loe et al found strong correlations between assessments of brightness and the illumination of a horizontal band 40° wide. 28,29 In a previous pilot study that utilised a scaled booth, the authors found MRSE correlated strongly with assessments of spatial brightness.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Many past studies have investigated the influence of spectral power distribution on spatial brightness, [15][16][17][18][19][20][21][22][23][24][25] Fotios et al provide a useful review. 26 Other studies have investigated the relationship between spatial brightness and light on a vertical plane 27 and also luminance within a defined field of view. 28, 29 Rea et al found illuminance on a vertical plane to correlate better with assessments of brightness than that of light on a horizontal plane.…”
Section: Introductionmentioning
confidence: 99%
“…The framework for a model of spectral sensitivity for scene brightness was developed through several initial laboratory studies and refined through subsequent studies (Rea et al, 2016;Besenecker et al, 2016;Besenecker and Bullough, 2017) and through analyses of independently published data sets (Fotios and Cheal, 2011;Zele et al, 2018;Bullough, 2015Bullough, , 2018. In summary, the spectral sensitivity for scene brightness appears to be influenced by short-wavelength (S) cones through the blue-yellow colour opponent channel, as well as by melanopsin in the intrinsically-photosensitive retinal ganglion cells; the influence of both of these channels also appears to increase with increasing radiance.…”
Section: Spectral Distributionmentioning
confidence: 99%